Distinct EMT programs control normal mammary stem cells and tumour-initiating cells - Ye, Xin (Nature, 2015)
Tumour-initiating cells (TICs) are responsible for metastatic dissemination and clinical relapse in a variety of cancers(1,2). Analogies between TICs and normal tissue stem cells have led to the notion that activation of the normal stem-cell program within a tissue serves as the major mechanism for generating TICs(3-7). Supporting this notion, we and others previously established that the Slug EMT-TF (EMT-inducing transcription factor), a member of the Snail family, is a master regulator of the gland-reconstituting activity of normal mammary stem cells (MaSCs), and that forced expression of Slug in collaboration with Sox9 in breast cancer cells can efficiently induce entrance into the TIC state(8). However, these earlier studies focused on xenograft models with cultured cell lines and involved ectopic expression of EMT-TFs, often at non-physiological levels. Using genetically engineered knock-in reporter mouse lines, here we show that normal gland-reconstituting MaSCs(9-11) residing in the basal layer of the mammary epithelium and breast TICs originating in the luminal layer exploit the paralogous EMT-TFs Slug and Snail respectively, which induce in turn distinct EMT programs. Broadly, our findings suggest that the seemingly similar stem-cell programs operating in TICs and normal stem cells of the corresponding normal tissue are likely to differ significantly in their details.